Does Earning Management Tend To The Accrual Basis Against The Cash Flow Basis? Assessing the Impact of Earning Management on Company Performance and Market Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Accountings Accrual basis is seen to seek favour in all corporate practitioners that manage earnings. There exists plethora of studies which focus on earning management mainly their risks. The study also leads to accounting literature as it reflects the tendency of market to the accounting accural basis as it's appears to motivate the earning management willingness. It further assessed the performance if any sample company with respect to the accrual-indicators vs. the cash-indicators along with their pricing spread in Iraq. The ownership of corporate in Iraq is one of the most dominant models of shareholder that turns the study unique with highlight of the motivation in earning management. The companies reveal preference for the Market for the accruals, as seen in the behavior of share pricing. We vision that the Study would better the perception of investors pertaining to the company's performance reliability as assessed by the earning. This is advantageous for the corporate finance and the accounting users both at local and global levels that help rationalize the motivation as seen behind the management manipulation of earning.